2015
DOI: 10.1088/0004-637x/800/1/40
|View full text |Cite
|
Sign up to set email alerts
|

HERSCHELSURVEY OF GALACTIC OH+, H2O+, AND H3O+: PROBING THE MOLECULAR HYDROGEN FRACTION AND COSMIC-RAY IONIZATION RATE

Abstract: In diffuse interstellar clouds the chemistry that leads to the formation of the oxygen-bearing ions OH + , H 2 O + , and H 3 O + begins with the ionization of atomic hydrogen by cosmic rays, and continues through subsequent hydrogen abstraction reactions involving H 2. Given these reaction pathways, the observed abundances of these molecules are useful in constraining both the total cosmic-ray ionization rate of atomic hydrogen (ζ H) and molecular hydrogen fraction (f H 2). We present observations targeting tr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

42
303
4
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 245 publications
(360 citation statements)
references
References 129 publications
42
303
4
1
Order By: Relevance
“…The observations were reproduced by models in which argonium is present only in the almost purely atomic diffuse ISM, with peak abundance at molecular fractions in the 10 −4 to 10 −3 range. Basically, high values of ζ favor its formation, consistent with analyses of OH + and H 2 O + , which trace slightly higher, but still low H 2 fractions (see, e.g., Hollenbach et al 2012;Indriolo et al 2015), whereas molecular fractions 10 −3 favor its destruction by the reaction with H 2 to produce Ar and H + 3 . Although ArH + abhors molecular clouds, it does rely upon a small amount of H 2 for its existence.…”
Section: Introductionsupporting
confidence: 78%
See 1 more Smart Citation
“…The observations were reproduced by models in which argonium is present only in the almost purely atomic diffuse ISM, with peak abundance at molecular fractions in the 10 −4 to 10 −3 range. Basically, high values of ζ favor its formation, consistent with analyses of OH + and H 2 O + , which trace slightly higher, but still low H 2 fractions (see, e.g., Hollenbach et al 2012;Indriolo et al 2015), whereas molecular fractions 10 −3 favor its destruction by the reaction with H 2 to produce Ar and H + 3 . Although ArH + abhors molecular clouds, it does rely upon a small amount of H 2 for its existence.…”
Section: Introductionsupporting
confidence: 78%
“…The large column densities of OH + with respect to H 2 O + were explained by both molecules residing preferentially in the largely atomic, diffuse interstellar medium (ISM), with the largest fractional abundances at a molecular fraction of Appendix A is available in electronic form at http://www.aanda.org around 0.04, and their unexpectedly large column densities require cosmic ray ionization rates ζ considerably larger than in the dense ISM (Hollenbach et al 2012;Indriolo et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The difference may result from the inaccuracy of the transition frequency of the H 2 O + line; it would amount to a correction of +1.0 MHz, to be added to the H 2 O + frequencies listed in Table 2. A correction was discussed by Neufeld et al (2010) and Indriolo et al (2015), who reported a value of +5 MHz.…”
Section: Correlations Between Different Moleculesmentioning
confidence: 98%
“…The detection of SH + toward W3 IRS5 was reported in . Foreground clouds of some high-mass objects in this selection at velocities offset from the YSO were analyzed by Indriolo et al (2015).…”
Section: Observationsmentioning
confidence: 99%
See 1 more Smart Citation